Тоғай ҳәм егислик экосистема территориясында тарқалған майда кемириўшилериниң изертлениў дәрежеси - Палўанова, Г.Ж (ILIM hám JÁMIYET, 2023)
The article examines the influence of anthropogenic factors on the biological diversity of the mammal fauna of the Lower Amudarya Delta Biosphere Reserve and its forest agrolandscape zone. It examines modern ecological processes of changes in the distribution of rodents and changes in the population dynamics of settlement complexes. It was also commissioned to conduct fundamen- tal research aimed at assessing their characteristics in the spread of especially dangerous diseases, including the plague.